Exploring Awareness and Perception of Do Not Resuscitate Orders in A Saudi Arabian General Population - Basubrain, Omar Sami (National Journal of Community Medicine, 2024)
Background: Do Not Resuscitate (DNR) orders are crucial, yet often misunderstood, medical directives. This study investigated public understanding and attitudes towards DNRs in Saudi Arabia. This study investigated public understanding and attitudes towards Do Not Resuscitate (DNR) orders in Saudi Arabia. Methods: A cross-sectional web survey was conducted among 416 Saudi residents aged 18 and above. The survey assessed knowledge, attitudes, and emotional responses related to DNR orders. Results: Over half (65.7%) lacked sufficient understanding of DNRs, highlighting a knowledge gap. While 56.8% grasped the meaning, less than half saw DNRs as beneficial for reducing pain or easing burdens on loved ones, indicating mixed attitudes. Decision-making preferences varied, with 49.1% advocating for medical professionals' involvement and 31% favouring family decisions. Personal experiences influenced understanding, with those having a family member's DNR order exhibiting higher comprehension. Conclusion: Significant knowledge gaps and mixed attitudes towards DNRs exist. Public education programs, improved patient communication, and culturally sensitive approaches are recommended to bridge this gap and empower individuals to make informed decisions.